Arts rupestres, écritures et protoécritures en Afrique : l’exemple du libyque - Jean-Loïc Le Quellec (Afriques)
Some pre- or protohistoric rock pictures in the Sahara have been interpreted as a protoscript that might have evolved into the Libyco-Berber script by integrating a stock of regional signs (tattoos, tribal marks, etc.). This article rejects this hypothesis.